Between Stigma and Reality: Colonial Narrative on Islamic Education and the Discourse on Worldly Knowledge in Malaya: (Antara Stigma dan Realiti: Naratif Kolonial Tentang Pendidikan Islam dan Perbahasan Ilmu Keduniaan di Tanah Melayu ) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The repercussion of colonialism on the Muslim society was not only limited to the administrative and structural aspects of society through the implementation of secular law and the Western administrative system. Above all, especially in Malaya, British colonial also introduced Western education system and colonial knowledge which was regarded as the best education system and incompatible with the progressive agenda. To ensure that Western education will be easily accepted by the Malays who were very prone to traditional religious education, the British colonial officials had created a narrative which describes the drawbacks of the traditional education system as well as instilled various negative stigma about the traditional education system. The clash of thoughts between groups of indigenous intellectuals who support or reject Western education had closed the initiative towards exploring the treasures and traditions of indigenous knowledge. Thus, this article aims to reassess the narrative constructed by the colonial British and to what extent it actually reflects the reality that existed in Malaya.